2014
DOI: 10.7740/kjcs.2014.59.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Lignan Content for Sesame Seed Across Origin and Growing Environments

Abstract: Sesame lignan, including sesamin and sesamolin has been reported to have various content according to accessions and environmental factors. The objective of this study were to analyze the lignan variation of 143 sesame accessions from core collection in Korea and to test the effects of growing years and locations on lignan and lipid content of Korea sesame elite lines. The results showed that the core sesame germplasm in Korea has broad variation of lignan content from 2.33 to 12.17 mg/g with an average 8.18 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The CV of sesamin in Wuchang and Yangluo was 65.12% and 58.03%, respectively, and that of sesamolin was 34.85% and 35.53%, respectively. These results are consistent with previous reports supporting that sesamin and sesamolin contents in seeds are influenced by environmental conditions [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The CV of sesamin in Wuchang and Yangluo was 65.12% and 58.03%, respectively, and that of sesamolin was 34.85% and 35.53%, respectively. These results are consistent with previous reports supporting that sesamin and sesamolin contents in seeds are influenced by environmental conditions [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…Sesamin and sesamolin contents in sesame seed are quantitative polygenic traits controlled by additive and dominance effects [ 13 , 14 , 15 ]. The sesamin and sesamolin contents vary broadly in sesame germplasms [ 16 , 17 , 18 ]. Their contents are influenced by other seed components, including oil, protein, and lignin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fatty acid profiles of the eleven black sesame varieties are categorized based on carbon saturation levels into saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA). The composition of these fatty acids in sesame seeds varies with the seed variety and environmental factors such as soil type, weather, and growing conditions [3,60,87,88]. The SFAs, such as palmitic acid (C16:0), margaric acid (C17:0), stearic acid (C18:0), arachidic acid (C20:0), and behenic acid (C22:0), were present in all the black sesame varieties.…”
Section: Fame Analysis By Gc-ms In Sesame Seedsmentioning
confidence: 99%
“…Several studies have reported that the contents of the main components in sesame seeds are different depending on the origin of production, cultivating environment, and varieties (2)(3)(4)(5). Some studies have discriminated the origins of sesame seed and sesame oil by combining the quality components with the statistical method according to the origin of sesame seeds (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%